Performance improvement in public organizations: How to enlarge ICT investments - Olli Martikainen; Jussi Autere; Markku Nurmela (The Research Institute of the Finnish Economy (ETLA), 2006)
The research analyses effective ways and means of improving the performance of public sector organizations. Etlatieto and TietoEnator have organized the study on the basis of interviews of key public sector managers in four Nordic countries. Special attention was paid to methods employing information and communications technologies (ICT). The first main result is contained in the conclusion, that performance objectives and methods of improving the public sector productivity are not similar to those in private industries. The justification for several public sector services and organizations comes from providing public goods like rule of law, collective security and social justice or putting limits to opportunistic behaviour. The second main result of the study lies in the assessment, that in public sector the services are often not codifiable. The user of the services assesses their quality based on the expectations and experiences. The third main result is that public sector organizations have underlying structures that make performance improvements more difficult than in private sector. In the private sector, all organizational levels usually get benefits from productivity improvements, but in the public sector incentive structures are not common to all actors. Based on the three basic results obtained the analysis suggests methods that can be used in pursuing higher performance in public sector.
Keywords: H11; O33; O38; L30; 330; Government performance; ICT diffusion; performance improvement; Informationstechnik; Investition; Innovationsdiffusion; Öffentlicher Sektor; Öffentliche Dienstleistung; Erfolgsfaktor; Finnland